2003
DOI: 10.1016/s0092-8674(03)00809-2
|View full text |Cite
|
Sign up to set email alerts
|

A “dock, lock, and latch” Structural Model for a Staphylococcal Adhesin Binding to Fibrinogen

Abstract: Gram-positive pathogens such as staphylococci contain multiple cell wall-anchored proteins that serve as an interface between the microbe and its environment. Some of these proteins act as adhesins and mediate bacterial attachment to host tissues. SdrG is a cell wall-anchored adhesin from Staphylococcus epidermidis that binds to the Bbeta chain of human fibrinogen (Fg) and is necessary and sufficient for bacterial attachment to Fg-coated biomaterials. Here, we present the crystal structures of the ligand bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
377
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 282 publications
(396 citation statements)
references
References 37 publications
19
377
0
Order By: Relevance
“…Using isothermal titration calorimetry and intrinsic tryptophan fluorescence, we confirmed that rClfB bound to the K10 tail region and measured the K D at 1.4 and 1.7 M, respectively. Leszczynski and Rose (27) The crystal structures of the minimal ligand-binding domains of ClfA, ClfB, and SdrG have been solved (28,29). 2 Each protein is composed of two domains N2 and N3 comprising variant Dev-IgG immunoglobulin folds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using isothermal titration calorimetry and intrinsic tryptophan fluorescence, we confirmed that rClfB bound to the K10 tail region and measured the K D at 1.4 and 1.7 M, respectively. Leszczynski and Rose (27) The crystal structures of the minimal ligand-binding domains of ClfA, ClfB, and SdrG have been solved (28,29). 2 Each protein is composed of two domains N2 and N3 comprising variant Dev-IgG immunoglobulin folds.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the wider Sdr family of surface proteins is predicted to have a similar modular design and Dev-IgG folds. The structure of the ligandbinding domain of SdrG both as an apoprotein and in complex with its peptide ligand showed that the protein has an open confirmation that allows access of the ligand to the binding cleft (29). A "dock lock and latch" hypothesis was proposed as the mechanism for ligand binding (29) 2 in which the ligand binds to the hydrophobic groove separating N2 and N3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B domains share signifi cant sequence similarities, including a sequence corresponding to EF-hand motif with an identity of over 35%, and two conserved Ca 2+ binding sites with 32% and 20% identity, respectively (Josefsson et al, 1998). Previous studies into the crystal structures of ClfA, ClfB and SdrG have revealed the molecular mechanism underlying ligand-binding by A region in these MSCRAMMs (Ponnuraj et al, 2003;Ganesh et al, 2008). Typically, MSCRAMMs have been reported to bind to fi brinogen, fi bronectin, neurexin and IgGs (Hartford et al, 2001;Deivanayagam et al, 2002;Barbu et al, 2010;Ganesh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%